Menggagas Teologi Perdamaian Sunnî-Shî‘ah di Indonesia - Agil Siradj, Said (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2013)
This article tries to analyze the phenomenon of Islamist violence in Indonesia due to the appeal between School of theology as was the case in Sampang, Madura. The conflict occurs because the Muslims can no longer recognize the differences between them, so that violence is a means of final settlement. Therefore, in this paper the author will try decoding problems between Sunni?s and Shiite?s School in Indonesia that I could find a way to peace. Because Sunni-Shi?ite actually are brothers who were born on the basis of the spirit of keeping the truth and glorifying the Islam thoroughly in various parts of the world. In this way, Muslims should be able to put this difference as the good graces and blessings of life.